Penerapan Ice Breaking dalam proses Pembelajaran sebagai Pengalaman Belajar yang Menyenangkan - Zuhaery, Muhammad; Dian Hidayati; Hidayat, Muhammad (Academy of Education Journal, 2024)
The application of ice breaking techniques in learning practices has been widely used by teachers in schools. This article will, among other things, answer the questions: what is the teacher's ability and understanding of learning using the Ice Breaking technique; and what are the steps in enjoyable learning. The purpose of this article is to help teachers understand learning by utilizing the Ice Breaking technique; and assist teachers in mastering and implementing steps in enjoyable learning. This research uses a type of qualitative research based on field studies in the form of case studies, taking the object of study as the implementation of the independent curriculum in two schools. Qualitative descriptive research with data collection techniques used namely observation, interviews and documentation. The analytical methods used are data collection, data reduction, data presentation and verification. The results of this research show that the application of ice breaking in students' learning in elementary schools can have an effect on increasing students' learning concentration during a fun learning process that runs well and is quite effective.